The Poetic Reconstitution of Place in The Poetry of Moya Cannon: Roots, Land, Home and Language - Collin, Luci (ABEI Journal, 2016)
The intricate relationship between place and the construction/ reshaping of personal and social identities is a matter of fundamental interest. The article discusses how, in her work, the Irish poet Moya Cannon (Dunfanaghy, County Donegal, 1956) explores the ’sense of place’, as presented by Seamus Heaney in his book Preoccupations (Faber 1980). One intends to analyse how this notion appears in Cannon’s poems and unfolds into other significant perspectives and themes such as: roots (past, heritage, historical bonds and fractures), land (landscape, sacramental sites), home (memory, local belonging, displacement) and language (linguistic awareness, linguistic dispossession).Keywords: sense of place, Moya Cannon, landscape, home.